Nilai-Nilai Kebudayaan dalam Grup Musik Patrol Arken di Kabupaten Jember - Haningdia Chintya Zaki Zabrina; Lusiana Agustiningtiyas; Sindi Ariska Dwi Agustin (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Patrol music group is a unique platform to explore and express various cultural values in musical works. Patrol music group often combines several cultural elements from various backgrounds to create a unique and interesting musical work. This research aims to explore the role of cultural values in the creation of patrol music and its impact on cultural appreciation among the society. The research also revealed that patrol music has the potential to increase tolerance, understanding, and appreciation towards cultural diversity. Patrol music encourages the audience to enjoy a rich cultural experience through music, making it possible to expand understanding of cultural diversity. In addition, patrol music often serves as a means to facilitate meetings among different community groups and provides opportunity to strengthen national awareness and cultural identity. This study points out that patrol music serves not only as a means of entertainment, but also as a means to deliver powerful messages related to the power of culture in building and developing social relationship, as well as promoting cultural identity. The results of this research can give insights into how cultural values of patrol music influence the cultural identity, both of individuals and the broaden society.